Clinical Estimation of Fetal Weight with Reference to Johnson’s Formula: An Alternative Solution Adjacent to Sonographic Estimation of Fetal Weight - Dongol, A.; Bastakoti, R.; Pradhan, N.; Sharma, N. (Kathmandu University Medical Journal, 2020)
Background Fetal weight estimation plays a significant role in the antenatal management of high risk pregnancies. It is also an important parameter for predicting the neonatal outcome and informs decision for the mode of intra-partum management of the pregnant women. Among the various methods of prenatal fetal weight estimation, the most commonly used are clinical estimation and sonography. Objective The objective of this study was to compare the accuracy of clinical estimation of fetal weight using Johnson’s formula and sonographic estimation with actual birth weight. Method This prospective study was conducted at Dhulikhel Hospital, Kathmandu University Hospital, from January 2017 to August 2018. The study included 335 pregnant women at term gestation. Result The estimation of fetal weight at term pregnancy using Johnson’s formula is as effective as sonological method. For clinical method, the fetal weight falls between 95 gm and 183 gm at 95% confidence interval. With respect to ultrasound method, the fetal weight is found to be 45 gm and 132 gm at 95% confidence interval at p value < 0.001. Conclusion Clinical estimation of fetal weight can be utilized as an alternative to sonological estimation in the management of labor and delivery. Johnson’s formula is a simple, easy, cost-effective, and universally applicable method to predict fetal birth weight and can be used anywhere by doctors, nurses, midwives and paramedics in centers where ultrasound is not available.